COVID-19 and a justice framework to guide tourism recovery. (November 2021) - Rastegar, Raymond; Higgins-Desbiolles, Freya; Ruhanen, Lisa
Highlights: COVID-19 is a justice issue representing years of unsustainable growth. It is now time to start imagining beyond tourism recovery. Discusses the opportunity to pause and reorientate tourism Provides a framework to make justice concerns central to tourism recovery